2021
DOI: 10.1088/1755-1315/640/4/042006
|View full text |Cite
|
Sign up to set email alerts
|

Research of the effect of willow-herb products in the preparation of kefir on the composition of fatty acids

Abstract: Fatty acids are important for the human body, and are involved in many biochemical processes. Unsaturated fatty acids are considered to be the most preferred. Some unsaturated fatty acids cannot be synthesized in the body and must be supplied with food. These unsaturated fatty acids include the omega 6 and omega 3 groups, the most significant of which are linoleic, arachidonic, and linolenic. Medicinal plants that contain a high amount of biologically active components can serve as a promising source of enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Известно, что микроорганизмы, входящие в состав заквасок для йогурта, в зависимости от физиологических особенностей образуют при сквашивании молока молочно-белковые сгустки с разными типами консистенции: колющиеся или вязкие с различной степенью тягучести [14]. Как известно, Streptococcus thermophilus в основном отвечает за производство кислоты, в то время как Lactobacillus bulgaricus придает йогурту своеобразный аромат [15].…”
Section: Introductionunclassified
“…Известно, что микроорганизмы, входящие в состав заквасок для йогурта, в зависимости от физиологических особенностей образуют при сквашивании молока молочно-белковые сгустки с разными типами консистенции: колющиеся или вязкие с различной степенью тягучести [14]. Как известно, Streptococcus thermophilus в основном отвечает за производство кислоты, в то время как Lactobacillus bulgaricus придает йогурту своеобразный аромат [15].…”
Section: Introductionunclassified
“…A study of French willow leaves use in the technology of cow's milk kefir showed its positive effect in the manufacture of kefir. Effect of added additive on fatty acid composition is described [5]. Other researchers also studied an antioxidant activity of yogurts and kefir from various unconventional types of milk.…”
Section: Introductionmentioning
confidence: 99%
“…The studies by other authors were aimed at developing formulations for a wide range of products, such as bakery products, sausages and soft drinks, using promising types of wild-growing medicinal raw materials, one of the components of which is willow herb [4].…”
mentioning
confidence: 99%